Knowledge, Attitude and Practice of Social Studies Teachers Towards Promoting Safe Spaces in the Academia: Basis for a Guide - Frendie S. Ladera; Novelyn M. Bualat; Bea Amelie Rebancos; Princess Diane Viray; Hernando L. Bernal Jr (RIRAI Publisher, 2024)
Safe space has become an imperative task for teachers because of its vital role in the teaching-learning process. Its meaning has developed over time due to its application in different instances. In academia, safe space is categorized as physical space, social space, and virtual space. Thus, this study aims to describe the knowledge, attitude, and practice of social studies teachers towards promoting safe spaces. The study utilized a descriptive quantitative approach consisting of 20 teachers as respondents from Ramon Magsaysay High School, Batasan Hills National High School, and Ilaya Barangka Integrated School. Findings indicate that the knowledge of the teachers in promoting safe space in three aspects is at a high level with a mean of 3.19 and a standard deviation of 0.66. Most of the time they practice promoting safe space in terms of physical space with a mean of 3.16 and standard deviation of 0.60, social space with a mean 3.28 and standard deviation of 0.69, and virtual space with a mean of 2.96 and standard deviation of 0.66. In terms of physical space, teachers give importance on routinary activities that ensure class and school are safe for the students. Further, in terms of social space, teachers practice values integration in their lessons on topics about respect for others regardless of their individual differences. Also, teachers are being held accountable for modeling this to the students such as avoiding discrimination and bias. Lastly, in terms of virtual space, teachers prepare students to be accountable for their actions online by reteaching the netiquette or dos and don’ts when using the internet. Findings of this study could be used as a guide by educational institutions when promoting safe space.